Plan de exportación de clavel en fresco de la empresa Santa Lucia SAS del municipio Combita hacia la ciudad de Miami - Estados Unidos (2023)
The present study focuses on an in-depth analysis considering the historical data provided by the company Santa Lucia SAS. It examines the possibilities of positioning in the international market by formulating an international marketing plan. Variables were proposed, and general data was collected to build selection matrices, aiming not only to determine the market segment to target but also strategically selecting the type of customer for exporting export-type carnations.